Biodegradable three-layer film derived from bovine gelatin - Martucci, Josefa Fabiana (2010)
Biodegradable three-layer gelatin film was obtained by heat – compression of piled dialdehyde starch (DAS) – cross-linked and plasticized-gelatin films (Ge-10DAS) outer layers and sodium montmorillonite (MMt) – plasticized – gelatin film (Ge-5MMt) inner layer. Multilayer film displayed a compact and uniform microstructure due to the highly compatible individual layers which could interact by strong hydrogen bonding. Lamination reduced moisture absorption and total soluble matter compared to the single layers while keeping transparency. Tensile strength and elastic modulus of the multilayer were 8.0 ± 1.3 MPa and 14.7 ± 2.4 MPa, which were significantly higher than values obtained for Ge-10DAS due to the contribution of the of the bio-nanocomposite inner layer. Elongation at break was not affected by lamination meanwhile it had a beneficial effect on barrier properties. Water vapor permeability (WVP) of the multilayer was 0.8 ± 0.1 × 10−13 kg m Pa−1 s−1 m−2 which was lower than those of the individual components whereas oxygen permeability was similar to that of Ge-5MMt (10.5 ± 0.4 cm3(O2) mm m−2 day−1) and lower than that of Ge-10DAS film.